Beyond the Limits to Growth New Ideas for Sustainability from Japan - Komiyama, Hiroshi (Science for Sustainable Societies,, 2014)
At a time when contemporary challenges seem to many to be insurmountable, this book offers an optimistic view of the future and provides a road map for societies to get there. Drawing upon extensive research and many years as a thought leader in environmental and sustainability issues in Japan and internationally, Hiroshi Komiyama analyzes the most pressing challenges to the attainment of sustainability of economically advanced nations and argues forcefully for Japan to lead them out of the present dilemma through active promotion of creative consumer and societal demand. He shows how an active industry–government–academic partnership can provide the environment needed to promote such new creative demand and illustrates its potential through presentation of a Platinum Society Network that was launched on a regional basis in Japan in 2010 to facilitate the solution of common issues through the exchange of information and ideas. What is perhaps most surprising about the text is its unwavering optimism supported by hard evidence, history, and insightful observation. Problems arising from new paradigms of the 21st century (what the author refers to as “exploding knowledge, limited Earth resources, and aging societies“) thwart sustainable development in advanced and developing countries alike. All countries will struggle with issues that evolve from these paradigms including diminishing resources, expanding budget deficits, and growing global environmental problems. This window on potential practical pathways and solutions should be of interest to all those engaged in seeking ways to meet these contemporary challenges.    .